The molecular subtypes of triple negative breast cancer were defined and a ligand-receptor pair score model was constructed by comprehensive analysis of ligand-receptor pairs - Pan, Weijun; Song, Kai; Zhang, Yunli; Yang, Ciqiu; Zhang, Yi; Ji, Fei; Zhang, Junsheng; Shi, Jian; Wang, Kun (Frontiers in Immunology, 2022)
Background Intercellular communication mediated by ligand-receptor interactions in tumor microenvironment (TME) has a profound impact on tumor progression. This study aimed to explore the molecular subtypes mediated by ligand-receptor (LR) pairs in triple negative breast cancer (TNBC), and found out the most important LR pairs to construct a prognostic risk model, and study their effect on TNBC immunotherapy. Methods LR pairs subclasses of TNBC were identified by consensus clustering based on LR Pairs in METABRIC dataset. Least absolute shrinkage and selection operator (LASSO) Cox regression and stepwise Akaike information criterion (stepAIC) were conducted to build a LR pairs score model. The relationship between LR pairs score and immune cell infiltration, stromal score and immune score associated with TME was analyzed, and the prediction of drug therapy and immunotherapy efficacy by LR pairs score was evaluated. Results According to expression pattern of 145 TNBC prognostic LR pairs, the samples were divided into three subclasses, which had different survival outcomes, copy number variation (CNV), TME immune cell infiltration, stromal score and immune score. The LR pairs score model constructed in the METABRIC dataset was composed of four LR pairs, and its predictive value for TNBC prognosis was verified in GSE58812 and GSE21653 cohorts. In addition, LR pairs score was negatively correlated with several immune pathways regulating immunity and immune score, and correlated with the sensitivity of anti-neoplastic drugs and the effect of anti-PD-L1 therapy. Conclusion Our study confirmed the impact of LR pairs on the molecular heterogeneity of TNBC, characterized three LR pairs subtypes with different survival outcomes and TME patterns, and proposed a LR pairs score system with predictive value for TNBC prognosis and anti-PD-L1 therapeutic effect, which provides a potential evaluation scheme for accurate treatment of TNBC.